Upaya Peningkatan Partisipasi dan Hasil Belajar IPA Melalui Pendekatan Scientific Model Crossword Puzzle pada Konsep Sistem Organisasi Kehidupan Siswa Kelas VIIA - Marsono Marsono (Universitas PGRI Semarang, 2021)
The purpose of this classroom action research is to increase participation and science learning outcomes on the concept of the Life Organization System through the Scientific approach of the Crossword Puzzle model for class VIIA SMP N13 Tegal students in the even semester of the 2018/2019 academic year, namely learning by using crossword puzzles (TTS) as tools used to embed science concepts. This research was conducted in 2 cycles, each cycle consisting of 3 meetings. The data collection method that will be used is observation, and activity documentation. The results of the analysis of student participation in the first cycle is 31.25% in the second cycle is 90.63%. And the analysis of student learning outcomes in the first cycle is 65.63% and the second cycle is 87.50%. Classically, this research is said to be successful because the participation and learning outcomes are above the minimum specified criteria, namely 85% active and 85% of students complete learning.